Teacher Learning in In-service Professional Development Insights from two In-service Training Programmes - Meganathan, Ramanujam (JOURNAL OF INDIAN EDUCATION, 2015)
This paper attempts to understand teacher learning through formal in-service professional development activities conducted by agencies like the National Council of Educational Research and Training (NCERT) and the State Council of Educational Research and Training (SCERT) in India. Based on the experiences of the professional development programmes conducted by NCERT at the national level and the SCERT of Rajasthan at the state level, this paper, through teachers’ pre-training and post-training opinions and reflections on various aspects of the training, brings out the needs and learnings of teachers in the training. Though both the training programmes showed some impact on the participating teachers and teacher learning during the training programmes, this does not ensure that the teachers will be implementing whatever has been learnt in the training. Three stages: pre-training period, while training period and immediate post-training period and the inputs by the training organisations and the trainers during all the three stages play a crucial role in making the programme effective and make an impact on the teachers. Materials for reading and worksheets for during and after activity also matter a lot for making a training programme a learning experience for the teachers.